2013
DOI: 10.1007/s00484-013-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 900 MHz electromagnetic field exposure on main male reproductive hormone levels: a Rattus norvegicus model

Abstract: This work analyzes the effects of radiofrequency-electromagnetic field (RF-EMF) exposure on the reproductive system of male rats, assessed by measuring circulating levels of FSH, LH, inhibin B, activin B, prolactin, and testosterone. Twenty adult male Sprague-Dawley rats (180 ± 10 g) were exposed to 900 MHz RF-EMF in four equal separated groups. The duration of exposure was 1, 2, and 4 h/day over a period of 30 days and sham-exposed animals were kept under the same environmental conditions as the exposed group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
5
35
0
Order By: Relevance
“…Several studies have demonstrated the negative impact of MW radiation exposure on male reproductive health which may affect male fertility . Reports are there mentioning the ill effects of short duration exposure to MW radiation on gonadotropin levels (FSH and LH), testicular morphology, histopathology, serum/plasma testosterone levels, sperm counts, and sperm viability . Studies demonstrate that short term exposure to 2.45 GHz MW radiation may lead to testicular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the negative impact of MW radiation exposure on male reproductive health which may affect male fertility . Reports are there mentioning the ill effects of short duration exposure to MW radiation on gonadotropin levels (FSH and LH), testicular morphology, histopathology, serum/plasma testosterone levels, sperm counts, and sperm viability . Studies demonstrate that short term exposure to 2.45 GHz MW radiation may lead to testicular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrate that rats exposed to two 3‐hr periods of daily cellular phone emissions for 18 weeks, exhibited a significantly higher incidence of sperm cell death along with abnormal clumping of sperm cells than control group rats (Yan et al, ). Long term exposure to 900 MHz RF‐EMF for a period of 30 days demonstrate a significant decreased in serum testosterone and inhibin B level and significant increase in FSH, LH Serum activin B, and prolactin level (Sepehrimanesh, Saeb, et al, ). Mobile phone radiation exposure also increased the number of non–progressive movement spermatozoa as well as DNA fragmentation in sperms (Gorpinchenko, Nikitin, Banyra, & Shulyak, ).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to 900 MHz radiofrequency electromagnetic field decreased testosterone level of male SpragueDawley rat [28]. Long-term exposure to mobile phone radiation leads to reduce in serum testosterone levels.…”
Section: Discussionmentioning
confidence: 87%
“…Exposure to static magnetic field (128 mT; 1 h/d for 30 d) decreased rat testosterone levels [29]. Exposure to mobile phone radiation 60 min/d for 3 mo significantly decrease the serum testosterone level of Wistar rats [28]. Exposed to 10 GHz microwave radiation for 2 h/day for 45 d significantly decreases the testosterone level of seventy day-old rats [30].…”
Section: Discussionmentioning
confidence: 99%